Tertiary hydrothermal activity and its effect on reservoir properties in the Xihu Depression, East China Sea - Yan Liu (KeAi Communications Co., Ltd., 2019)
Abstract Three large-scale episodes of volcanic activity occurred during the Tertiary in the Xihu Depression, located in the East China Sea. Intermediate-felsic magmas intruded along faults and the associated hydrothermal fluids resulted in the hydrothermal alteration of the clastic country rock. To better describe reservoir characteristics, reservoir samples were subjected to the following investigations: thin section examination, scanning electron microscope-energy dispersive spectrometer analysis (SEM–EDS), fluid inclusion homogenization temperature tests, vitrinite reflectance measurements, and X-ray diffraction. The results of this study provide evidence of the following hydrothermal alteration phenomena: brittle fracturing, clastic particle alteration, precipitation of unique hydrothermal minerals (celestite, zircon, apatite, barite, and cerous phosphate). The presence of abnormally high temperatures is indicated by fluid inclusion analysis, the precipitation of high-temperature authigenic minerals such as quartz, illite alteration, and anomalous vitrinite reflectance. Two aspects related to hydrothermal effects on reservoir properties have been investigated in this study: (1) Deep magmatic hydrothermal fluids carry large amounts of dissolved carbon dioxide and sulfur dioxide gas. These fluids percolate into the country rocks along fault zones, resulting in dissolution within the sandstone reservoirs and the development of significant secondary porosity. (2) Magma intrusions increase the temperature of the surrounding rocks and accelerate the thermal evolution of hydrocarbon source rocks. This results in the release of large amounts of organic acids and carbon dioxide, leading the dissolution of the aluminosilicate minerals and volcanic fragments in the reservoirs, and the generation of significant secondary porosity.